Fairy tail. 51 - Mashima, Hiro, 1977- (Fairy tail., 2015)
"The black magic cult Avatar's plans to summon Zeref are well underway, but their Operation Purify will cost countless lives. To stop them, Gray joins forces with Erza and infiltrates Avatar, while Zeref the Black Wizard reveals another piece of his shocking past. Finally, after a year of being apart, Natsu, Lucy, Happy, Gray, and Erza return as Fairy Tail's strongest team! Can their bravery and bonds of friendship stand against Avatar?!"--Back cover.